RELATIONSHIP BETWEEN FIXED ORTHODONTIC TREATMENT AND WEIGHT LOSS – A SURVEY (International Journal of Food and Nutritional Sciences, 2022)
Fixed orthodontic treatment has a potential impact on patient’s life which leads to changes and restrictions in their dietary habits which is causing difficulty in consuming hard foods in which the masticatory ability of the patient is depleted. The current study aims to assess the relationship between fixed orthodontic treatment and weight loss. MATERIALS AND METHODS: the survey was conducted for patients undergoing orthodontic treatment, which included 10 questions. The total study participants were 100 in number, which included both males of 39 and females of 61. RESULTS: The results showed that 58% of the patients had weight loss after the orthodontic treatment. Among the patients who reported of weight loss 51% had a weight loss of about 1-2kg and about 19% had weight loss of about 2-3 kg. CONCLUSION: The above study confirms that changes in dietary patterns, reduction in the quantity of food intake and weight are recognised among patients undergoing fixed orthodontic therapy.